The investigation of the lake water/groundwater interaction in the hyporheic zone of a groundwater-dependent lake (Lake Płotki, Poland) - Matusiak, Magdalena; Marciniak, Marek; Owsianny, Paweł; Dragon, Krzysztof (Quaestiones Geographicae, 2025)
The article presents the investigation of vertical hydraulic gradients (VHGs) between surface water and groundwater in the hyporheic zone of Lake Płotki. The results indicate the presence of lake shoreline sections where groundwater recharges the lake (indicated by upwelling zones) and sections where lake water filtrates into the groundwater system (indicated by downwelling zones). The research indicates the occurrence of hyporheic exchange in the lake shoreline. The spatial extent of the upwelling and downwelling zones appears to depend on the groundwater circulation system and fluctuations in groundwater levels. The local geology was found to influence the boundary between the lake’s recharge and discharge zones. The results presented significantly contribute to the investigation of the lake water/groundwater interaction and to the study of the lake system recharge and discharge conditions by groundwater. This is especially important in the regions where investigation of overall hydrogeological conditions (especially the groundwater flow pattern) is relatively poor. This research may have practical implications for the effective monitoring of water resources in the region.